1996
DOI: 10.1016/0042-6989(95)00326-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Attentional Speed-up in the Motion Induction Effect

Abstract: Motion induction is the illusory motion within an elongated stimulus, such as a bar or a line, when it is preceded by a priming stimulus next to one of its ends. Motion is away from this primer. The presentation of two priming spots at both ends of a stimulus bar results in motion away from both spots with a collision in the center of the bar. With a sufficiently long delay between the spots, motion will be seen only as away from the second spot. Similarly, in a bar with a luminance gradient an illusory motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Moreover, if a bar appears that is bright at one end and progressively dims along its length, motion occurs from the bright to the dim end (von Grünau, Racette, & Kwas, 1996); this occurs despite the fact that the entire bar presentation creates only a contrast increase. Furthermore, the motion is in the direction from the larger increase towards the smaller, so it is towards a tendency to decrease.…”
Section: Brief Overview Of Illusory Line Motionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, if a bar appears that is bright at one end and progressively dims along its length, motion occurs from the bright to the dim end (von Grünau, Racette, & Kwas, 1996); this occurs despite the fact that the entire bar presentation creates only a contrast increase. Furthermore, the motion is in the direction from the larger increase towards the smaller, so it is towards a tendency to decrease.…”
Section: Brief Overview Of Illusory Line Motionmentioning
confidence: 99%
“…The fitting of a function to the percept scores in order to extract ILM PSE opens the door for many additional experimenter degrees of freedom, such as what function to fit (log linear as currently employed or Weibull as in von Grünau, Racette et al, 1996), how to fit it (least squares, maximum likelihood), and the criterion for deciding if a function provides a good fit. All of these decisions open up additional questions of appropriateness of the choice, which can complicate interpretation, become a source of distraction, and reduce the simplicity of comparison between studies.…”
Section: Quantifying Ilmmentioning
confidence: 99%
See 1 more Smart Citation
“…It has further been asserted that the orienting of attentional mechanisms toward the location of the luminance increase is the cause of the perceived motion within the line (Hikosaka et al, 1993b;von Grünau, Racette, & Kwas, 1996). Studies of temporal order judgments have shown that the orienting of attention produces an acceleration of arrival times in the vicinity of the attended locus (Schneider & Bavelier, 2003;Shore, Spence, & Klein, 2001;Stelmach & Herdman, 1991).…”
mentioning
confidence: 99%
“…Hence, it was hypothesized that the sensation of motion evoked by the subsequently flashed line could result from sequential suprathreshold activation mimicking real motion drawing away from the local cue. [17][18][19][20] Figure 2(c) shows cortical responses (in V1 of an anaesthetized cat) evoked by the spot when it was flashed alone. 20 Consistent with spreading along horizontal connections, postsynaptic subthreshold activity propagated at a speed of ∼0.1 m∕s (Refs.…”
Section: -16mentioning
confidence: 99%